The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1007/bf00171727
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic effects of serotonin (5-HT) receptor ligands in pigs: stimulation of 5-HT2 receptors induces malignant hyperthermia

Abstract: In pigs, the serotonin-2 (5-HT2) receptor agonist 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI), 0.8 mg/kg, induced "psychotic" behaviour (e.g., grimacing, backward locomotion, blank stare) and a muscular syndrome, which is known as malignant hyperthermia (MH) in pigs and humans. This syndrome is characterized by generalized skeletal muscle rigidity, leading to an increase in body temperature, marked acidosis, hyperkaliaemia, cyanosis and elevation of lactate, carbon dioxide and the muscle enzyme creatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 40 publications
1
32
0
1
Order By: Relevance
“…These findings, however, do not exclude an additional involvement of enhanced synthesis of IPs by activation of receptors which are G-protein-linked or coupled to tyrosine kinases (Berridge, 1993;Foster, 1994). As shown by the present data, 5-HT seems not to be critically involved in the enhancement of IPs at least in the halothane-induced MH crisis, whereas in MH triggered by a 5-HT2 receptor agonist this mechanism may play an important role (L6scher et al 1990a;Wappler et al 1996). Possibly, already moderate increases of IPs induced by 5-HT2A receptor agonists may be sufficient to induce contractures of skeletal muscle as found in MHS pigs (LOscher et al 1990a) or in muscle specimens of MH susceptible patients (Wappler et al 1996) because of a hypersensitive response of MHS skeletal muscle to IP3 induced release of calcium (Lopez et al 1995).…”
Section: Discussionmentioning
confidence: 37%
“…These findings, however, do not exclude an additional involvement of enhanced synthesis of IPs by activation of receptors which are G-protein-linked or coupled to tyrosine kinases (Berridge, 1993;Foster, 1994). As shown by the present data, 5-HT seems not to be critically involved in the enhancement of IPs at least in the halothane-induced MH crisis, whereas in MH triggered by a 5-HT2 receptor agonist this mechanism may play an important role (L6scher et al 1990a;Wappler et al 1996). Possibly, already moderate increases of IPs induced by 5-HT2A receptor agonists may be sufficient to induce contractures of skeletal muscle as found in MHS pigs (LOscher et al 1990a) or in muscle specimens of MH susceptible patients (Wappler et al 1996) because of a hypersensitive response of MHS skeletal muscle to IP3 induced release of calcium (Lopez et al 1995).…”
Section: Discussionmentioning
confidence: 37%
“…Several other studies have shown similar results in that stimulation of 5-HT 2A receptors by specific agonists cause hyperthermia in laboratory animals (3,32,37). Currie et al (13) evaluated the role of neuropeptide Y (NPY) on 5-HT receptors in relation to food intake and energy metabolism in rats.…”
Section: Discussionmentioning
confidence: 83%
“…Ein weiterer Mechanismus könnte im Zusammenhang mit dem ᭤ Serotoninrezeptorsystem gesehen werden, da einige Serotoninrezeptorsubtypen, u. a. der ᭤ Serotonin-2-Rezeptor, an den Inositolphosphatstoffwechsel gekoppelt sind [2], und nach Applikation eines Serotonin-2-Rezeptoragonisten bei MH-Disposition signifikant früher eine Muskelkontraktur am isolierten Skelettmuskelpräparat registriert werden kann [41]. Darüber hinaus konnte nach Gabe von Serotonin-2-Rezeptoragonisten bei Schweinen eine MH-Episode ausgelöst [20] bzw. durch Prämedikation mit einem Serotonin-2-Rezeptorantagonisten die Entwicklung einer Halothan-induzierten MH-Krise verhindert werden.…”
Section: Pathophysiologie Der Rezeptor-und "Second-messenger-systeme"unclassified